User-Generated Content and Buying Behavior on Instagram: The Moderating Effect of Brand Trust - Ali Ashraf; Muhammad Irfan Ali; Farhan Tariq (`, 2025)
The current project is aimed at mapping the impact of user generated content as far as consumer buying behavior is concerned. It also analyzes the moderating effect of brand trust and consumer purchasing behavior in regards to user generated content. The methodology adopted was survey and the tool of data collection was questionnaire but the simple random sampling technique was adopted to obtain the respondents. The results of the research indicate that brand trust is a good relationship with purchasing behavior of buyers. Later in the paper, the researcher furthered by stating that knowledge of people about user generated content is hugely related to customer buying behavior and moderating effects of brand trust. The results also showed that the UGC is a powerful influence, which encourages the user to make purchasing activities. Moreover, the established positive association between UGC and brand trust highlights the significance of user-generated content in building and reinforcing trust among consumers. Keywords: User Generated Content, Media, Instagram, Buying Behavior, Brand Trust